Implementing harm reduction kits in an office-based addiction treatment program - Margaret Shang; Brent Thiel; Jane M. Liebschutz; Kevin L. Kraemer; Ariana Freund; Raagini Jawa (BMC, 2023)
Abstract Background The rising rates of drug use-related complications call for a paradigm shift in the care for people who use drugs. While addiction treatment and harm reduction have historically been siloed in the US, co-location of these services in office-based addiction treatment (OBAT) settings offers a more realistic and patient-centered approach. We describe a quality improvement program on integrating harm reduction kits into an urban OBAT clinic. Methods After engaging appropriate stakeholders and delivering clinician and staff trainings on safer use best practices, we developed a clinical workflow for universal offering and distribution of pre-packaged kits coupled with patient-facing educational handouts. We assessed: (1) kit uptake with kit number and types distributed; and (2) implementation outcomes of feasibility, acceptability, appropriateness, and patient perceptions. Results One-month post-implementation, 28% (40/141) of completed in-person visits had at least one kit request, and a total of 121 kits were distributed. Staff and clinicians found the program to be highly feasible, acceptable, and appropriate, and patient perceptions were positive. Conclusions Incorporating kits in OBAT settings is an important step toward increasing patient access and utilization of life-saving services. Our program uncovered a significant unmet need among our patients, suggesting that kit integration within addiction treatment can improve the standard of care for people who use drugs.